Physiological and biochemical responses of Aeluropus lagopoides and Aeluropus littoralis to drought stress (Open Access Journal of Medicinal and Aromatic Plants, 2012)
The effect of water deficit on two species of Aeluropus (Aeluropus lagopoides and Aeluropus littoralis) was examined to study the physiological and biochemical responses of these perennial halophytes. Vegetatively propagated plants were subjected to drought stress by withholding water for 5, 11 and 18 days. Dry and fresh weight, free proline, malonaldehyde content, levels of potassium and sodium ions and pigments as well as antioxidant enzymes were monitored during the drought period. Results indicated that these two species expressed differential response to water deficit based on severity of stress. By maintaining higher dry and fresh weight, proline levels and lower malonaldehyde A. lagopoides was found to be more tolerant. Whereas, A. lagopoides had more active salt excreting glands that resulted in more efficient removal of Na+. Though peroxidase activity increased in both A. lagopoides and A. littoralis, the increase was more in A. littoralis. While, polyphenol oxidase activity in A. lagopoides was higher than A. littoralis, except on day 18. In conclusion, A. lagopoides has a higher potential to adapt to arid and semi-arid conditions and is a candidate of choice for both soil stabilizer and forage.